Território: agente educador na construção da cidadania - Barboza, Danilo Praxedes (2023)
The research aims to demonstrate that the territory, simultaneously physical and symbolic, is a fundamental aspect for a citizenship, fair and transformative education. To this end, will be analyzed the work developed by the Curumim Program, a non-formal educational proposal by Sesc São Paulo aimed at children aged 7 to 12, which has been innovating in the offering of educational, cultural and leisure activities for over 35 years. From the basic documents of the Curumim Program and interviews with educators working at Sesc Consolação, located in the historic center of São Paulo, will be observed the experiences, possibilities, and limits of working with the territory. The main theoretical references of the research are: the critical and transformative educational perspective of Paulo Freire (1987, 1996, 2021); the conception of territory presented by Milton Santos (2004, 2007, 2020, 2021a, 2021b); and the conception of curricular justice and its dimensions of care, meaningful knowledge for life and democratic coexistence presented by Branca Jurema Ponce (COSTA; ARAÚJO; PONCE, 2023; PONCE, 2016, 2018; PONCE; ARAÚJO, 2019, 2021, 2021; PONCE; LEITE, 2019; PONCE; NERI, 2018). From the analysis of documents and interviews with Curumim educators, it is demonstrated that the development of educational activities with children in the territory enables the enrichment of the sociocultural repertoire of all subjects involved in educational practice, promotes critical thinking, consciousness, and social responsibility